The Implementation of Project Based Learning (PBL) in Improving Students’ Speaking Skill at SMA Yadika Kopandakan II - Ceisy N. Wuntu; Yolanda Singal; Olga A. Rorintulus (International Journal of English and Applied Linguistics (IJEAL), 2022)
This study was intended to find out whether the Project Based Learning implementation is effective in improving students’ speaking skill. The researcher used quantitative research by giving pretest and posttest in measuring students’ productive skill especially in speaking. There were 27 students as the respondents. Third grade student of natural science became as the experimental class and third grade student of social science became as controlled class. The mean score showed that the pretest was 51.18. On the other hand, the mean score showed that the posttest was 74,71. The percentage and frequency of the students’ scores of pretest for experimental class showed that nine or 53% got average score, seven or 41 % got poor score and one or 0,06 % student got very poor score. On the other hand, the researcher used project based learning method in the classroom then the result for pretest showed that three or 18 % students who got very good score, six or 35 % students who got good score, and eight or 47% students who got average score. There was significant difference between the pretest and the posttest. Based on the result, there was significant difference between experimental class and controlled class on their speaking achievement. It means that the implementation of Project Based Learning was beneficial in improving students speaking ability in reporting procedure text.